Application of ADDIE Learning Model Assisted by Desmos Application to Improve Ability to Understand Mathematical Concepts - Jihan, Jihan Rofifah; Hendriana, Benny (Universitas Islam Ahmad Dahlan (UIAD), 2023)
This study aims to improve students' understanding of mathematical concepts using the application of the ADDIE learning model assisted by the desmos application. This research is a Classroom Action Research. The research subjects consisted of 36 students of class X-D SMAN 83 Jakarta. Data collection techniques used description test instruments, observation sheets, and documentation. Data analysis used quantitative and qualitative descriptive analysis. Researchers conducted initial observations (pre-cycle) and two learning cycles. An observer assessed the activities of educators and students in each cycle. The results stated that students experienced an increase in the ability to understand mathematical concepts seen from the pre-cycle percentage of 13.89%, cycle I of 66.67%, cycle II of 83.33% and reached the KKM score ≥78 and in accordance with the research target of 80%. This is supported by the activities of students and the activities of educators who also experienced an increase in each cycle in the good category. So it can be said that using the application of the ADDIE learning model assisted by the desmos application can improve the ability of students' understanding of mathematical concepts in trigonometry material.